2015
DOI: 10.3892/ol.2015.3081
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and prognosis-associated factors of non-small cell lung cancer exhibiting symptoms of bone metastasis at the time of diagnosis

Abstract: Abstract.The present study aimed to analyze the clinical characteristics and prognosis-related factors of non-small cell lung cancer (NSCLC) patients with bone metastases at the time of diagnosis. A total of 46 NSCLC patients with skeletal metastases at the time of diagnosis from Anhui Provincial Hospital and Anhui Provincial Cancer Hospital Affiliated to Anhui Medical University (Hefei, China) between February 2010 and February 2012 were investigated retrospectively. The median age was 58 years, with a range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
0
12
1
1
Order By: Relevance
“…Squamous cell carcinoma was found to be an independent risk factor for SREs at the time of NSCLC diagnosis. It has been reported that the frequency of distant metastases is higher in adenocarcinoma (3,16,17); there are discrepancies between those findings and the findings of the present study. It was also observed that the incidence rate of SREs was significantly higher in squamous cell carcinoma compared with that in adenocarcinoma patients at the time of NSCLC diagnosis.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Squamous cell carcinoma was found to be an independent risk factor for SREs at the time of NSCLC diagnosis. It has been reported that the frequency of distant metastases is higher in adenocarcinoma (3,16,17); there are discrepancies between those findings and the findings of the present study. It was also observed that the incidence rate of SREs was significantly higher in squamous cell carcinoma compared with that in adenocarcinoma patients at the time of NSCLC diagnosis.…”
Section: Discussioncontrasting
confidence: 57%
“…Non-small-cell lung cancer NSCLC is the third most common cause of bone metastases following breast and prostate cancer (2). It has been reported that 84.8% of patients exhibit multiple skeletal metastases at the time of NSCLC diagnosis, which cause complications including bone pain, pathological fractures, spinal cord compression and dysmotility (3). There are differences in the prognosis of NSCLC patients with and without bone metastases (4,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERβ has been investigated in numerous cancers including prostate, breast, kidney (Yu et al., 2013), colon (Dey et al., 2013), endometrium (Han et al., 2015), ovary (Ciucci et al., 2014, Suzuki et al., 2008) bladder (Hsu et al., 2013) and non-small cell lung cancer (He et al., 2015, Luo et al., 2015) but in many cases, the findings are predicated on non-specific reagents. As such, a re-evaluation of ERβ expression and biology is needed using reliable, specific reagents.…”
Section: Discussionmentioning
confidence: 99%
“…При Оригінальні дослідження / Original Researches этом наиболее агрессивной гистологической формой РЛ считается мелкоклеточный гистологический ва-риант заболевания [16]. Вместе с тем среди больных РЛ с костными метастазами соотношение аденокар-циномы и плоскоклеточной карциномы (немелко-клеточных РЛ) составило 3 : 1 [10]. Как свидетельст-вует выполненный нами однофакторный дисперсион-ный анализ, метастатическое поражение костно-су-ставного аппарата связано с локализацией патологи-ческого процесса (D = 2,22; p = 0,039), формой забо-левания (центральная, периферическая) (D = 26,33; p < 0,001), некоторыми гистологическими варианта-ми РЛ (аденокарцинома, плоскоклеточная карцино-ма) (D = 26,33; p < 0,001) и наличием легочного ком-прессионного синдрома (D = 3,08; p = 0,005).…”
Section: результаты и их обсуждениеunclassified